Numerical and experimental study of the ultimate strength of a monopile structure. (1st September 2019) - Yeter, B.; Garbatov, Y.; Guedes Soares, C.
Highlights: The ultimate strength of a tubular structure subjected to a bending moment is analysed. Three specimens are designed for the experimental test. The moment-curvature and the stress-strain relationship of the tested specimens are studied. The tested specimens are also evaluated based on the finite element method. The results of the finite element analysis and the experiments are compared and discussed. Abstract: The objective of the present work is to analyse the ultimate strength of a tubular structure subjected to a bending moment. The tubular monopile structures are experimentally tested as well as the nonlinear finite element analysis is performed. Three specimens are designed for the experimental test by taking into consideration the typical ranges of the monopile support structures used in offshore wind turbines. The moment-curvature and the stress-strain relationship of the tested specimens are studied. The tested specimens are also evaluated numerically based on the finite element method employing a nonlinear FE analysis. The finite element analysis accounts for the nonlinearities associated with the geometry and material. The geometrical imperfections are introduced to the structure together with the initial stress arisen in the process of fabrication. The results obtained from the finite element analysis and the experimental tests are compared to each other and discussed.